Molecular aspects of Besnoitia besnoiti-driven bovine neutrophil extracellular trap formation - Espinosa Espinoza, Gabriel Rodolfo; Justus Liebig University Giessen (My University, 2026)
Recent studies have collectively advanced our understanding of bovine neutrophil responses against tachyzoite stages of Besnoitia besnoiti, an apicomplexan parasite responsible for the re-emerging cattle disease bovine besnoitiosis. A central focus of the current work was to fill some gaps on the molecular mechanisms underlying the parasite-driven formation of neutrophil extracellular traps (NETs), a key innate effector mechanism. Therefore, in a first investigation, the role of neutrophil purinergic signalling was studied, revealing that B. besnoiti tachyzoites significantly induce NET formation without altering intracellular or extracellular ATP concentrations in bovine PMN. Despite this finding, extracellular supplementation with ATPγS, a non-hydrolyzable ATP analog, significantly enhanced NET release - specifically anchored NETs - whilst native ATP failed to do so. This response depended on the P2X1 purinergic receptor since treatments with the specific antagonist NF449 (IC50 = 1.27 μM) inhibited both NET formation and PMN clustering triggered by tachyzoite exposure. In contrast, pharmacological blockade of other purinergic receptors (P2Y2, P2Y6, P2X4, P2X7) did not affect NET formation, thereby highlighting a selective role for the P2X1 puringergic receptor in B. besnoiti tachyzoite-driven NET formation. Metabolic assays using Seahorse technology further revealed increased oxygen consumption rates (OCR) in tachyzoite-exposed PMN, while ATPγS treatment led to enhanced extracellular acidification rates (ECAR), suggesting mitochondrial involvement and metabolic adaptation during the early steps of the NETotic process. A second study complemented above-mentioned findings by focusing on the calcium/calmodulin-dependent protein kinase kinase 2 (CAMKK)/AMPK signalling axis and its link to autophagy. B. besnoiti and Toxoplasma gondii tachyzoite exposure induced rapid phosphorylation of AMPK in bovine PMN within 30 minutes, a response mirrored by the AMPK activator AICAR. Referring to signalling pathways, AMPK phosphorylation correlated with an activation of the upstream regulator CAMKK in both B. besnoiti and T. gondii-exposed PMN and upregulation of the downstream autophagy-related protein ULK-1 (but not Beclin- 1) in the case of B. besnoiti-exposed PMN, indicating a selective autophagic signature. Notably, AICAR treatments alone led to enhanced NET formation without compromising PMN viability. However, in B. besnoiti tachyzoite-exposed PMN, AICAR co-treatments failed to affect oxidative response. Moreover, AICAR co-treatments induced additive effects on tachyzoite-induced NET formation. In the case of T. gondii, this NET formation response further depended on MAPK and store-operated calcium entry (SOCE) pathways, as shown by reduced DNA release upon MAPK- and SOCE inhibition. These findings suggest that autophagy and AMPK signaling signify parallel, ROS-independent pathways involved in the support of B. besnoiti-driven NET formation. A third line of investigation explored the role of extracellular vesicles (EVs) as potential modulators of B. besnoiti-driven bovine neutrophil responses. To obtain EVs from differential sources, EVs were isolated from B. besnoiti tachyzoites, infected and non-infected bovine umbilical vein endothelial cells (BUVEC), and tachyzoite-exposed PMN. Their identity was confirmed via nano-flow cytometry, by EV markers like CD9 and CD81, and morphologically by transmission electron microscopy. When bovine PMN were exposed to differential EVs, particularly those derived from tachyzoites and infected BUVECs induced a significant NET release. This was validated microscopically by the presence of extracellular DNA structures adorned with histones and neutrophil elastase - hallmarks of classical NETs. Interestingly, PMN-derived EVs failed to trigger NET formation. Moreover, none of the different EV types drove changes in the neutrophil metabolic profile (oxidative and glycolytic responses) or ROS production in exposed bovine neutrophils, as assessed by Seahorse analysis and chemiluminescence assays, respectively. These findings indicated a NADPH oxidase (NOX)- independent mechanism of EV-induced NET formation. Furthermore, cytokine analyses revealed that EVs from infected BUVECs selectively induced IL-1β and IL-6 secretion in PMN, without influencing CXCL8 production, thereby pointing towards a tailored inflammatory response modulated by EVs of distinct cellular origin.
Drivers of NETs in Besnoitia besnoiti infection
Keywords: Neutrophil; Besnoitia besnoiti; Extracellular traps; ddc:630